Analisis Gaya Belajar Siswa SMK dalam Belajar Bahasa Inggris - I Jro Riana; Luh Made Dwi Wedayanthi; Kadek Dwi Pebriyanti (Universitas Maritim AMNI Semarang, 2023)
This research aims to analyze the learning styles of 11th-grade students in Class MP 2 at SMK N 1 Bangli in the context of learning English. The findings indicate that the majority of students have a preference for kinesthetic learning style, followed by auditory and visual learning styles. Despite the dominance of the kinesthetic learning style, some students also show tendencies towards auditory and visual learning styles. Meanwhile, the research identifies several learning difficulties faced by students, such as a lack of motivation, basic English language proficiency, and limited school resources. To address these challenges, teachers and schools are advised to create an environment that supports students' learning motivation, pay special attention to mastering basic English language skills, and enhance students' access to quality learning resources, including the use of technology such as utilizing smartphones for learning activities. Learning Styles, English Language Learning, Analysis of Students' Learning Styles